Fenomena Upwelling di Perairan Spermonde Sulawesi Selatan - Dyan Viegas Wibisono; Supriyatno Widagdo; Viv Djanat Prasita (Jurnal Riset Kelautan Tropis (Journal Of Tropical Marine Research) (J-Tropimar), 2022)
Spermonde waters are waters that surround the Spermonde islands with shallows located in the southwest of South Sulawesi which is in the tropics and crossed by the equator which causes these waters to experience two different seasons, namely the west and east monsoons. The purpose of this study was to analyze the upwelling phenomenon in spermonde waters. Spermonde waters in the east monsoon (June-August) have the potential for upwelling because they have strong winds and currents so that there is an Ekman transport that causes the deflection of the current to move from southeast to west. Indications of upwelling can be seen from the increase in the temperature and salinity of the water mass from the inside that occurs at all stations so that it is strong for upwelling to occur. The pattern of chlorophyll-a concentrations in the Mediterranean and upwelling seas that occur is weak because the highest chlorophyll is near the coast due to the influence of river water and several other industrial activities so that off shore area shaven ottoo high chlorophyll whichis associated with adecrease in sea surface temperature.